Keuangan Negara (Ekonomi Publik): Teori dan Praktek - Sukanto Reksohadiprodjo (Magister Administrasi Publik, 1996)
The writing attempts to claril• the emergence of the branches of the science state lands/fi¬nances (public• economy), which first originated in the 17 and 18 couturier in France and Britain. 7he dissatisfaction which followed the development of this theeny led to the emergence of the •os¬sh thcaist• which was contained in the teachings of Adam Smiths 's Wealth of nations published in ;776. From these two teach:nips was burn /hough, of low the 'vie government hi the econinui. should emu ny he. There ivas indeed an increasing awareness about the importance of the theory of government finance because of increasing intensity of government intervemion in the market mechanism which it is believed, con interfere with the development of the private sector. Meanwhile on the other hand, government intervention in regulating the economic activities is very desirable to de¬veloping commies like Indonesia, throng/ fir instance, development plans. This interference of governmeni in the operations of the market mechanism. especially in developing commies, are ulti¬mately carried out in foam of government prcnerts which are then controlled with utmost transpa¬rency in order that ciliciency in the public economy can be achieved, so that it can give us confidence to compete with other commies during this ern of globalization.